Development of Digital Technology Competency of Entrepreneurs in Roi Et Province by the Process of Participation of Local Government Organizations to Raise the Sustainable Community Economy - Boontosang, Benchawan (Dhammathas Academic Journal, 2026)
This research aims to 1) to study the problems and needs of household economy and community economy. 2) to study the developing digital technology competencies of entrepreneurs 3) to study the use of digital technology competency in the occupations of entrepreneurs. This study used a qualitative research methodology, using participatory action research methodology and in-depth interviews. The research area is Roi Et Municipality. Key informants were selected as representatives of each group using specific methods, totaling 40 people include executives and personnel of Roi Et Municipality, community leaders, citizens and entrepreneurs. Data analysis using descriptive content analysis. The results of the study: 1. The problems and needs of household economy and community economy included low income and debt, living expenses and consumer goods prices, and minimum wage and employment problems. Economic needs include promoting additional careers for local people, supporting funds for occupations. Providing knowledge and skills development for the people, providing markets for selling and distributing products, promoting tourism, reducing the cost of living, and promoting community products. 2. The developing digital technology competency of entrepreneurs in Roi Et Municipality includes Designing training activities to develop digital technology competencies of entrepreneurs in collaboration with Roi Et Municipality. Setting criteria for selecting entrepreneurs to participate in the project in collaboration with Roi Et Municipality. Selecting target groups according to the criteria in collaboration with Roi Et Municipality. Determining the training topics and setting the training date in collaboration with Roi Et Municipality. Training workshops according to the topics, date, time, and location specified, along with evaluating digital competencies for entrepreneurs in the Roi Et Municipality area. 3. The use of digital technology competence in the occupations of entrepreneurs in Roi Et Municipality. It was found that the use for creating careers, the use for further development of products and services, the use for generating income and self-reliance, the use for upgrading the community economy.